2009
DOI: 10.1073/pnas.0809804106
|View full text |Cite
|
Sign up to set email alerts
|

Fetal ethanol exposure increases ethanol intake by making it smell and taste better

Abstract: Human epidemiologic studies reveal that fetal ethanol exposure is highly predictive of adolescent ethanol avidity and abuse. Little is known about how fetal exposure produces these effects. It is hypothesized that fetal ethanol exposure results in stimulusinduced chemosensory plasticity. Here, we asked whether gestational ethanol exposure increases postnatal ethanol avidity in rats by altering its taste and odor. Experimental rats were exposed to ethanol in utero via the dam's diet, whereas control rats were e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
131
1
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(140 citation statements)
references
References 47 publications
7
131
1
1
Order By: Relevance
“…However, since in that study the familiarization procedure involved the ingestion of relatively large amounts of ethanol, sufficient to induce pharmacological effects, it may be concluded that the reported effect was the consequence of an appetitive association between ethanol's flavor and its reinforcing properties, rather than solely an effect of familiarization. Likewise, when comparing the present results with those of studies involving prenatal ethanol exposure in which increased intake, enhanced palatability and even odor preference were observed (Abate et al, 2008;Chotro et al, 2007Chotro et al, , 2009Spear & Molina, 2005;Youngentob & Glendinning, 2009), it remains clear that in all those studies the experience with ethanol necessarily involved a reinforcer in addition to ethanol's flavor.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…However, since in that study the familiarization procedure involved the ingestion of relatively large amounts of ethanol, sufficient to induce pharmacological effects, it may be concluded that the reported effect was the consequence of an appetitive association between ethanol's flavor and its reinforcing properties, rather than solely an effect of familiarization. Likewise, when comparing the present results with those of studies involving prenatal ethanol exposure in which increased intake, enhanced palatability and even odor preference were observed (Abate et al, 2008;Chotro et al, 2007Chotro et al, , 2009Spear & Molina, 2005;Youngentob & Glendinning, 2009), it remains clear that in all those studies the experience with ethanol necessarily involved a reinforcer in addition to ethanol's flavor.…”
Section: Discussionmentioning
confidence: 49%
“…In another study with rat fetuses, no differential responsiveness to a mint flavor was found after analyzing eleven behavioral categories of the fetal response as a function of familiarity (Smotherman & Robinson, 1985). With the flavor of ethanol, which is a complex stimulus with gustatory, olfactory and irritant components, it has been found that prenatal exposure induces increased intake and/or enhanced palatability of ethanol in infant and older rats (Abate, Pueta, Spear, & Molina, 2008;Chotro, Arias, & Laviola, 2007;Youngentob & Glendinning, 2009) (Chotro, Arias, & Spear, 2009). Although in most of this research exposure to ethanol also involved the presence of reinforcing consequences, it should be pointed out that when the contiguity of ethanol's flavor with reinforcement was explicitly avoided, no changes were observed either in ethanol consumption (Arias & Chotro, 2006;Chotro & Alonso, 2003;Chotro & Arias, 2003;Chotro et al, 2009) or in reactivity to its flavor (Arias & Chotro, 2005;Dominguez, Chotro, & Molina, 1993;Molina & Chotro, 1991).…”
Section: Introductionmentioning
confidence: 93%
“…Extensive basic research in animal models demonstrates that prenatal or early neonatal alcohol exposure alters a variety of later behavioral (Abate, et al, 2008; Becker et al, 1993; 1993; Chotro & Arias, 2006; Middleton et al, 2009; March et al, 2009), consummatory (Chotro et al, 2007; Diáz-Cenzano et al, 2014; Miranda-Morales et al, 2014; Shea et al, 2012; Youngentob & Glendinning. 2009), pharmacological (Diáz-Cenzano et al, 2014; Pautassi et al, 2012), biochemical (Middleton et al, 2009), and physiological (Eade et al, 2010; Taylor et al, 1981; Weinberg et al, 1995) responses to alcohol.…”
Section: Introductionmentioning
confidence: 99%
“…2009), pharmacological (Diáz-Cenzano et al, 2014; Pautassi et al, 2012), biochemical (Middleton et al, 2009), and physiological (Eade et al, 2010; Taylor et al, 1981; Weinberg et al, 1995) responses to alcohol. Possible means by which PAE influences postnatal responses to and ingestion of alcohol include altered chemosensory experiences of alcohol and/or learning about the rewarding (or aversive) properties of alcohol cues in utero (e.g., Arias & Chotro, 2005; Chotro & Arias, 2006; Chotro et al, 1991; 2009; March et al, 2009; Pautassi et al, 2012; Youngentob & Glendinning, 2009); ideas articulated well in the theoretical review by N. Spear and Molina (2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation